2022
DOI: 10.17275/per.22.85.9.4
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Pre-Service Teachers’ Behavioral Intentions to Use Web 2.0 Gamification Tools

Abstract: This study aimed to investigate the pre-service teachers' behavioural intentions about using gamification tools and the critical factors affecting their usage. The data were collected from 313 pre-service teachers from two large-scale universities in Turkey through a questionnaire with seven constructs: perceived ease of use, usefulness, self-efficacy, enjoyment, computer anxiety, attitude, and behavioural intention. Firstly, students were trained on the gamification method and Web 2.0 gamification tools (Kaho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 95 publications
1
3
0
Order By: Relevance
“…The findings are consistent with those of other writers on the pleasure and motivation of students (Donkin & Rasmussen, 2021;Pryke, 2020). A few academics have previously analyzed the benefits and drawbacks of adopting mobile devices in higher education (Fuchs, 2022;Sprenger & Schwaninger, 2021;Turan et al, 2019). Some researchers worry that this tech-based approach will have unfavorable results for educators (Li et al, 2019) and pupils (High et al, 2022).…”
Section: Discussionsupporting
confidence: 88%
“…The findings are consistent with those of other writers on the pleasure and motivation of students (Donkin & Rasmussen, 2021;Pryke, 2020). A few academics have previously analyzed the benefits and drawbacks of adopting mobile devices in higher education (Fuchs, 2022;Sprenger & Schwaninger, 2021;Turan et al, 2019). Some researchers worry that this tech-based approach will have unfavorable results for educators (Li et al, 2019) and pupils (High et al, 2022).…”
Section: Discussionsupporting
confidence: 88%
“…The use of Kahoot Media in the course has a positive impact on the knowledge and skills they acquire (Licorish et al, 2018). The use of Media Kahoot as an educational game in the classroom can minimize distractions when lecturer teach online (Turan et al, 2022), thereby increasing the quality of teaching and learning beyond that provided in conventional classrooms. Media a Kahoot as a learning medium without reducing the objectives, content and quality of learning content (Rafnis, 2018).…”
Section:  Results and Discussionmentioning
confidence: 99%
“…Study this only focus aspect cognitive, which is the aspect cognitive include: Remembering (C1). Understanding (C2), Applying (C3), Analyzing (C4), Evaluating (C5), Creating (C6) (Quadir & Chen, 2019;Syafryadin et al, 2021;Turan et al, 2022).…”
Section:  Introductionmentioning
confidence: 99%
“…Because of gamification, they were not bored or tired while learning journalism. Turan et al (2022) state that perceived enjoyment can be considered an independent factor independent of behavioral intention. It was found that participants experienced no anxiety while using Web 2.0 gamification tools.…”
Section: Discussionmentioning
confidence: 99%